Social Capital in the Capital Region of the Archipelago (Case Study of Telemow Village, Sepaku District, North Penajam Paser Regency, East Kalimantan) - A. Ismail Lukman; Laily Fadhilah; Arwin Sanjaya; Ahmad Sidik (JED (Jurnal Etika Demokrasi), 2022)
Most of the people of Telemow village are immigrants, but can live in harmony and peace. This study aims to determine the social capital that becomes the grip and glue of the community in Telemow village. The type of research used is qualitative research and is described descriptively. Determination of informants by means of purposive sampling and saturated sampling technique. In obtaining research data, the researcher used observation, interview, and documentation techniques. The collected data is then analyzed using interactive model analysis techniques, namely the data is reduced, then presented, and finally concluded or verified. The researcher uses data/source triangulation in examining the data. The results of the study are: 1) Forms of social capital, namely a) Mutual cooperation. Gotong royong activities are in accordance with needs and are not scheduled and the funding comes from non-governmental organizations in the form of environmental cleaning activities, repairing small-scale village infrastructure, and helping communities affected by disasters such as illness, accidents, and so on. In addition, there is also a scheduled mutual cooperation that is carried out simultaneously in all village areas every year and the funding is sourced from the Village Fund called Bulan Bakti. b) Formal and informal forums. Formal forums include Gapoktan, Pokdakan, PKK, KB Village, and Dasawisma. Meanwhile, informal forums take the form of patrols, sports, and Gerakan Sedekah Harian. 2) Factors that influence social capital are trust, norms, and social networks. The social capital that is built in the Telemow village community becomes the glue that is able to arouse a sense of concern, tolerance, togetherness, trust, and brotherhood among the community so as to create harmony, unity, and oneness. The more often people meet, gather, and share stories, the potential to reduce conflict.